2007
DOI: 10.1007/s11746-007-1157-y
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Interesterification of Palm Stearin and Coconut Oil by a Dual Lipase System

Abstract: Enzymatic interesterification of palm stearin with coconut oil was conducted by applying a dual lipase system in comparison with individual lipase-catalyzed reactions. The results indicated that a synergistic effect occurred for many lipase combinations, but largely depending on the lipase species mixed and their ratios. The combination of Lipozyme TL IM and RM IM was found to generate a positive synergistic action at all test mixing ratios. Only equivalent amount mixtures of Lipozyme TL IM with Novozym 435 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…Ibrahim et al 6 also observed a synergistic effect for the Lipozyme TL IM -RM IM dual system in the interesterification of palm stearin and coconut oil.…”
Section: Biodiesel Synthesis Using Mixtures Of Commercial Immobilizedmentioning
confidence: 91%
See 4 more Smart Citations
“…Ibrahim et al 6 also observed a synergistic effect for the Lipozyme TL IM -RM IM dual system in the interesterification of palm stearin and coconut oil.…”
Section: Biodiesel Synthesis Using Mixtures Of Commercial Immobilizedmentioning
confidence: 91%
“…The use of combined enzyme resulted in higher amount of ester produced when the total amount of lipases was lower than 7 wt.%. Ibrahim et al 6 demonstrated that a positive interaction between two mixed lipases does not always happen. According to these authors, the interactive effect differs for different lipase combinations and mixing ratios, and some experiments with blends of different lipases showed an antergic effect.…”
Section: Biodiesel Synthesis Using Mixtures Of Commercial Immobilizedmentioning
confidence: 99%
See 3 more Smart Citations